2013
DOI: 10.1111/hdi.12106
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting failure of AV “fistula first” policy in the elderly

Abstract: An arteriovenous fistula (AVF) is the preferential hemodialysis (HD) access. The goal of this study was to identify factors associated with pre-dialysis AVF failure in an elderly HD population. We used United States Renal Data System + Medicare claims data to identify patients ≥ 67 years old who had an AVF as their initial vascular access placed pre-dialysis. Failure of the AVF to be used for initial HD, was used as the outcome. Logistic regression model was used to identify factors associated with AVF failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 40 publications
3
55
0
Order By: Relevance
“…Our results concurred with those of previous studies in finding that the parameters old age and female gender were predictors of unnecessary AVF creation [11]. A simulation study also demonstrated that aging increased the risk of unnecessary AVF creation, mainly due to the competing risk of death [14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results concurred with those of previous studies in finding that the parameters old age and female gender were predictors of unnecessary AVF creation [11]. A simulation study also demonstrated that aging increased the risk of unnecessary AVF creation, mainly due to the competing risk of death [14].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, an increasing number of studies have described the adverse effects of early AVF creation among CKD patients, such as high rates of vascular access complication and death before dialysis commencement [8,9,10,11,12,13]. A US study found that among primarily stages 3 and 4 CKD patients (overall, 78%), the AVF failure and mortality rates during the predialysis periods were 63 and 23%, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…Other reports have noted that women and black race are independent risk factors for AVF failure. [32][33][34][35][36][37] Given the higher failure rate in women and blacks as opposed to men and whites, it is possible that placing a fistula earlier in these highrisk subgroups conferred a better outcome by enabling the longer time needed for maturation. However, the longer time before HD initiation may necessitate the performance of endovascular or surgical interventions to achieve adequate patency.…”
Section: Discussionmentioning
confidence: 99%
“…When adjusted using a proportional hazards model that treated death as a competing event, black patients were more likely to start dialysis than die compared with white patients (HR, 1.14; 95% CI, 1.02 to 1.27; P=0.02) ( Table 2). The patients with the highest comorbidity scores (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) were least likely to initiate hemodialysis compared with those with lower scores (0-4 and 5-10) ( Table 1). When adjusted using a proportional hazards model that treated death as a competing event, the comorbidity scores were no longer associated with likelihood of starting dialysis ( Table 2).…”
Section: Patient Outcomes After Predialysis Vascular Access Creationmentioning
confidence: 99%
“…Applying uniform vascular access guidelines to elderly individuals may not be appropriate because of the competing risk of death, 7,10 the high rate of AVFs that fail to mature, 11 and poor vascular access outcomes in the elderly population. 12 Thus, the objective of this study was to use a large representative United States population to identify the proportion of elderly patients with advanced CKD with predialysis AVF or arteriovenous graft (AVG) creation who survive to initiate dialysis, die before dialysis initiation, or survive dialysis free during 2 years of follow-up.…”
mentioning
confidence: 99%